Between Marriage and Economic Independence: A Qualitative Study on Women’s Life Choices from the Perspective of Liberal Feminism - Citra Septia Dewi; Rizki Ananda; Ika Arinia Indriyany (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research is motivated by the shifting social perspectives on marriage, where women no longer view marriage solely as the primary goal of life, but increasingly consider individual autonomy and economic independence. Although social norms often still place women in domestic roles, access to education and employment opportunities has provided women with greater space to determine their own life choices, including the choice to delay marriage or not marry at all. The purpose of this study is to identify the considerations women make when choosing not to marry, analyze the relationship between economic independence and this life choice, and examine the phenomenon through the perspective of liberal feminism. This research uses a qualitative method with a case study approach to explore the subject’s experiences in depth. The findings show that economic independence provides women with stronger bargaining power, so the decision not to marry is no longer considered a social deviation, but rather a mature reflection of individual rights and financial freedom. The implications of this study emphasize the need to redefine gender roles in modern society to be more inclusive of women’s diverse life choices without negative stigma. This research contributes to the enrichment of literature in family sociology and gender studies, particularly in understanding the dynamics of women’s independence in the contemporary era.